Влијанието на користењето на интернетот врз продуктивноста на претпријатијата во Република Македонија - Фирфов, Огнен (Економски факултет, УКИМ, Скопје, 2018)
With the development of information technology in 70’s and 80’s, as well as with the enhanced spreading of the Internet in 90’s and broadband Internet in 00’s, in parallel the topcis of interest for potential economic effects emerged. One of the most interesting topics out of this topics was and still is the change and increase of productivity as a result of Internet usage. Today in the periods of economic crises, the interest for for the economic influence of ICT and Internet is even more stronger due to the opinion that investments in broadband infrastructure can influence economic growth and help to the countries to emerge out of the economic crises. The text analyses scientific work related to this topics, and then main knowledge and models of use are being extracted and presented, both on macro and level of industries. After that, based on this models and local research in R.Macedonia, there is an attempt to synthesise the influence of the Internet to the local economy and to different industries. Additionally, effects of the Internet on the organizational changes are being analysed. Qualitative and quantitative researches have been made with management representatives of different companies from different industries. From this researches conclusions are drawn related to the influence of the Internet on the productivity on the whole economy and separate industries, as well as for the influence to the organizational changes and business models of companies. By the management perception, in some industries pretty big increase, bigger than 1 % is shown for the increase of the broadband penetration of 10%, while in some other industries this growths are considerably smaller. This growth is being connected with the propulsiveness of the typical industry and it’s dependence of the regular Internet usage. Similar tendencies are noticed also with the influence of the Internet to the organisations, change of business models, influence on the human resource structure, etc. The opinion for the growth of the whole economy for growth of the broadband Internet penetration of 10% is mostly concentrated around 1%. At the end of the text, general conclusions and summary thoughts related to the whole engagement are being drawn.
Influence of the Internet usage on the enterprise productivity in Republic of Macedonia
Докторска дисертација одбранета во 2018 година на Економскиот факултет во Скопје, под менторство на проф. д–р Љубомир Дракулевски.
Keywords: Internet, Productivity, Orgаnisations, Management, Business Model